Soybean (Glycine max L.) Response to Fungicides in the Absence of Disease Pressure - W. James Grichar (International Journal of Agronomy)
Field studies were conducted during the 2010 and 2011 growing seasons along the Texas Upper Gulf Coast region to study the effects of fungicides on soybean disease development and to evaluate the response of four soybean cultivars to prothioconazole plus trifloxystrobin and pyraclostrobin. In neither year did any soybean diseases develop enough to be an issue. Only NKS 51-T8 responded to a fungicide treatment in 2010 while HBK 5025 responded in 2011. Prothioconazole plus trifloxystrobin increased NKS 51-T8 yield by 23% in 2010 while in 2011 the yield of HBK 5025 was increased 14% over the unsprayed check. No yield response was noted with pyraclostrobin on any soybean cultivar. Only prothioconazole + trifloxystrobin applied to either NKS 51-T8 or DP5335 in 2010 resulted in a net increase in dollars per hectare over the unsprayed check of the respective cultivar. In 2011, under extremely dry conditions, all fungicides with the exception of prothioconazole + trifloxystrobin applied to HBK 5025 resulted in a net decrease in returns over the unsprayed check.